Asymmetric return dynamics and stock price crash risk: Evidence from a quantile regression analysis of an emerging market - Arif, Unbreen; Ahmad, Bilal; Rizvi, Fizza; Azhar, Sarah (Economic Journal of Emerging Markets, 2026)
Purpose — Understanding extreme downside risk is particularly important in emerging equity markets, where higher market volatility, lower liquidity, and weaker information environments make stock prices more vulnerable to sudden, severe crashes. This study examines downside risk, stock price crash risk, and lower-tail return dynamics using firm-level stock return data for firms listed in the Pakistan Stock Exchange over the period 2014–2024. Method — Using panel regression and quantile regression techniques, the study investigates the determinants of crash risk and assesses the predictive role of downside risk for future equity returns. Findings — The results indicate that downside risk is strongly associated with a higher likelihood of extreme negative return realisations, while its effect on average returns remains limited. Quantile-based estimates further show that the impact of downside risk intensifies substantially in the lower tail of the return distribution, highlighting pronounced return asymmetries. These patterns persist across both financial and non-financial firms, although their magnitude varies with market conditions. Implications — The results carry important implications for investors, regulators, and risk managers concerned with downside protection and the identification of early warning signals in emerging equity markets.Originality — This study provides new firm-level evidence from an emerging equity market by jointly examining downside risk, crash risk, and return tail behaviour within a unified empirical framework by using quantile regression.